The beginnings of electron microscopy. - Hawkes, P. W.; Hytch, Martin (Advances in imaging and electron physics, 2022)
"The Beginnings of Electron Microscopy - Part 2, Volume 221 in the Advances in Imaging and Electron Physics series, highlights new advances in the field, with this new volume presenting interesting chapters on Recollections from the Early Years: Canada-USA, My Recollection of the Early History of Our Work on Electron Optics and the Electron Microscope, Walter Hoppe (1917-1986), Reminiscences of the Development of Electron Optics and Electron Microscope Instrumentation in Japan, Early Electron Microscopy in The Netherlands, L.L. Marton, 1901-1979, The Invention of the Electron Fresnel Interference Biprism, The Development of the Scanning Electron Microscope, and much more."--Publisher's web page, viewed April 26, 2022